Now: A Post-Romantic Countertextuality of the Contemporary. Issue 2 (August 2015) - Corby, James
<x content-type="archive" xml:space="preserve">Abstract</x> In this essay James Corby questions the dominant future-oriented nature of the ethical turn of theory and philosophy in the final decades of the twentieth century and its aesthetic influence. Focusing in particular upon the ethical position of Jacques Derrida, Corby argues that the desire to avoid the closure of the contemporary and to preserve the possibility of difference by cultivating a radical attentiveness to that which is 'to come' often risks a too complete disengagement from the present, leading to an empty and ineffectual ethical stance that actually preserves the contemporary situation that it seeks to open up. Corby makes a case for this theoretical investment in the possibility of a non-contemporary (typically futural) rupture as being understood as forming part of a far-reaching romantic tradition. In opposition to this tradition he sketches a post-romantic alternative that would understand difference as an immanent, rather than imminent, matter. He argues that this should be considered congruent with a countertextual impulse oriented not towards a revelatory futurity, but, rather, towards the possible displacements, dislocations, and transformations already inherent in the contemporary. The final part of the essay develops this idea, positioning countertextuality as the articulation of alternative contemporaries. In this regard, the literature of the future is not 'to come', it is already here. The challenge is to recognise it as such, and this means being prepared to modify and change the conceptual apparatus that guides us in our thinking of literature and the arts.